Under the southern sky [large type] - Harvey, Kristy Woodson (Thorndike press large print core, 2021)
"Recently separated Amelia Buxton, a dedicated journalist, never expected that uncovering the biggest story of her career would become deeply personal. But when she discovers that a cluster of embryos belonging to her childhood friend Parker and his late wife Greer have been deemed "abandoned," she's put in the unenviable position of telling Parker--and dredging up old wounds in the process. Parker has been unable to move forward since the loss of his beloved wife three years ago. He has all but forgotten about the frozen embryos, but once Amelia reveals her discovery, he knows that if he ever wants to get a part of Greer back, he'll need to accept his fate as a single father and find a surrogate. Each dealing with their own private griefs, Parker and Amelia slowly begin to find solace in one another as they navigate an uncertain future against the backdrop of the pristine waters of their childhood home, Buxton Beach. The journey of self-discovery leads them to an unforgettable and life-changing lesson: Family--the one you're born into and the one you choose--is always closer than you think. From "the next major voice in Southern fiction" (Elin Hilderbrand, #1 New York Times bestselling author), Under the Southern Sky is a fresh and unforgettable exploration of love, friendship, and the unbreakable ties that bind"--